2015
DOI: 10.1080/15384047.2015.1070991
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of KRAS mutations in circulating tumor cells from patients with metastatic colorectal cancer

Abstract: Background: Quantification of Circulating Tumor Cells (CTCs) as a prognostic marker in metastatic colorectal cancer (mCRC) has already been validated and approved for routine use. However, more than quantification, qualification or characterization of CTCs is gaining importance, since the genetic characterization of CTCs may reflect, in a real time fashion, genetic profile of the disease. Objective: To characterize KRAS mutations (codon 12 and 13) in CTCs from patients with mCRC and to compare with matched pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…Counting was made per milliliter of blood. Cells were considered CTCs if they were negative for CD45 and presented with hyperchromatic nucleus, irregular shape, and high cytoplasm–nucleus ratio (>0.5) 9. Positive results for peripheral blood micrometastases were defined as CTCs ≥5/7.5 mL 6…”
Section: Methodsmentioning
confidence: 99%
“…Counting was made per milliliter of blood. Cells were considered CTCs if they were negative for CD45 and presented with hyperchromatic nucleus, irregular shape, and high cytoplasm–nucleus ratio (>0.5) 9. Positive results for peripheral blood micrometastases were defined as CTCs ≥5/7.5 mL 6…”
Section: Methodsmentioning
confidence: 99%
“…More novel is the use of CTCs for personalized treatments [29]. In a variety of cancers, mutation analysis for common variants in CTCs is being evaluated to assist in treatment selection [30,31]. While still exploratory, this avenue is gaining recognition in the medical research community.…”
Section: Liquid Biopsy: Technologies Advancing Personalized Medicinementioning
confidence: 99%
“…It is unclear at this time if this heterogeneity affects outcomes, but it is possible that failure of EGFR-inhibition in patients thought to have a KRAS wild-type CRC (determined from an arbitrary section of the primary tumor) may be partly due to the presence of a KRAS -mutated subclonal population. In a recent study, Buim et al demonstrated that KRAS mutations derived from CTCs correlate with mutations in the primary tumor with a concordance of 71 % of matched cases ( P = 0.017) [61]. These studies suggest that CTCs may play a role as a surrogate for primary tumors and metastasis when genomic analysis is necessary and the primary tumor is not available or as a means to serially monitor tumor genomes that can evolve during relapse, treatment, and progression.…”
Section: Introductionmentioning
confidence: 99%